Quine, Goodman, Putnam: the Harvard Philosophical School - Laktionova, Anna (Sententiae, 2022)
The article offers formal and doctrinal reasons that prove the existence of the “Harvard Philosophical School” as a real historico-philosophical phenomenon. The author includes Willard Van Orman Quine, Nelson Goodman, and Hilary Putnam in this school. The aim of this article is to compare the conceptualism, relativism and anti-realism of Quine, Goodman and Pantem, on the basis of (neo)pragmatic tendencies in their philosophical studies. Formal reasons: all these philosophers were professors at Harvard University; in addition, Quine was a teacher of Goodman and Putnam, Goodman was a teacher of Putnam. Doctrinal reasons: (1) Quine, Goodman, and Putnam, each in his own specific pragmatic way, stood on the positions of relativism, anti-realism, conceptualism, and tried to separate themselves from “cultural relativism”; (2) common touchstone concepts and tendencies in particular in their philosophical investigations are: conceptual scheme, indeterminacy of translation, internal criteria, ontological relativity and others; (3) the obvious analogy between Quine's standards of similarity, Goodman's standards of correctness, and standards for Putnam's conceptual schemes. Thus, we have strong reasons to consider Quine, Goodman and Putnam as representatives of a common philosophical school. The role played in their doctrines by the ideas of William James, who also taught at Harvard, at least hypothetically allows us to expand the boundaries of this school.